Analysis of Students' Learning Interest in Geography Subjects - Putri, Elma Salsabila; Buwono, Sri; Harjanti, Diah Trismi (Jurnal Pendidikan Sosiologi dan Humaniora, 2024)
The aim of this research is to find out how students are interested in learning about the subject of geography in class . The form of research used in this research is qualitative research with descriptive research methods. Data collection techniques in this research used observation, interviews and documentation methods. The data collection instruments used were observation sheets, documentation and interview guides. Data analysis uses the Miles and Huberman model which consists of data reduction, data presentation, drawing conclusions. The research results show that class XI IIS students are interested in geography subjects. Students' interest in learning can be seen through 4 indicators, namely, feelings of happiness, students' attention, students' involvement, and students' willingness to learn. So students are said to be interested in geography subjects because they meet the four indicators of learning interest.